(untitled) (Research, Society and Development, 2022)
The aim of this article is a literature review about the Human Right to Adequate Food content from an analysis of its ethnic-racial dimension. This review was part on first author’s master’s dissertation, in Post-graduation Program in Sustainable Rural Development, from The Western Paraná State University - Unioeste. For this purpose, a contextualization of the Human Right to Adequate Food was presented, and then the research presents the importance of an ethnic-racial dimension of this right for its full realization. It was concluded that indigenous peoples, Traditional People and Communities and the black population are the population groups most vulnerable to Food and Nutritional Insecurity and to protect, respect and promote the Human Right to Adequate Food of these people/communities includes the right to land/territory, the right to self-determination, the promotion of sustainable food systems, and respect for their cultures, knowledge and traditions.